2016
DOI: 10.1039/c6nr04859e
|View full text |Cite
|
Sign up to set email alerts
|

Constructing bulk defective perovskite SrTiO3nanocubes for high performance photocatalysts

Abstract: Defects (Ti or oxygen vacancies) have been demonstrated to promote the charge separation process in TiO based photocatalysts. Particularly, the bulk defects within a certain concentration can give a great enhancement for both light absorption and charge separation efficiency. In this report, we explored a one-step molten salts route to synthesize SrTiO nanocubes with bulk defects (Ti doped) by using SrCO as a Sr source, and TiO and Ti powder as Ti sources. The amount of defects can be tuned by changing the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
61
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 52 publications
3
61
1
Order By: Relevance
“…Structural analysis of the samples performed by X‐ray diffraction (XRD) and Raman spectroscopy is shown in Figure . The main diffraction lines of all samples (Figure a), independently of the Mg content, can be assigned to cubic SrTiO 3 with orientations of (110), (111), (200), (211), and (220) located at 2 θ of 32.58°, 40.1°, 46.61°, 57.9°, and 67.95°, respectively . The XRD pattern of Sr 1.25 Mg 0.3 TiO x indicates that a phase‐pure cubic SrTiO 3 ‐like material was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Structural analysis of the samples performed by X‐ray diffraction (XRD) and Raman spectroscopy is shown in Figure . The main diffraction lines of all samples (Figure a), independently of the Mg content, can be assigned to cubic SrTiO 3 with orientations of (110), (111), (200), (211), and (220) located at 2 θ of 32.58°, 40.1°, 46.61°, 57.9°, and 67.95°, respectively . The XRD pattern of Sr 1.25 Mg 0.3 TiO x indicates that a phase‐pure cubic SrTiO 3 ‐like material was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Surface photovoltage spectroscopy (SPS) is ap owerful tool that was used to further characterize charge separation at the nanoscale. [14,20] Spectraw ere recorded on powder samples sandwiched between an indium tin oxide (ITO) electrode anda Cu substrate. The surface photovoltage (SPV) response of ZCS and S-treated ZCS are shown in Figure3a.…”
Section: Resultsmentioning
confidence: 99%
“…Sun et al. found that defective SrTiO 3 can increase the charge separation efficiency by five times compared with common SrTiO 3 . Typically, the defect energy level is located below the CB and/or above the valance band (VB) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface photovoltage (SPV, Fig. S4) presents a positive photovoltage response, indicating the generated carriers can efficiently be separated and rapidly migrate to the surface [34][35][36].…”
mentioning
confidence: 99%